Development and Modification of Self-assembled Mesenchymal Stem Cells Aggregates for Musculoskeletal Tissue Engineering - 노수진 (The Graduate School, Ajou University, 2024)
재생의학과 조직공학은 모두 생체 외에서 조직과 장기 구성체를 제작하여 생체 조직의 기능을 회복하거나 대체하는 것을 목표로 한다. 자가 조립 기술은 생체 모방, 확장성 및 다양한 세포 유형에 대한 적응성과 같은 이점을 제공하여 세포가 기능적 조직으로 조직화하는 선천적인 능력을 활용한다. 이 기술은 구조와 기능 측면에서 고유한 조직과 매우 유사한 구조를 생성할 수 있는 가능성을 가지고 있다. 이러한 향상된 생체 모방은 특히 적절한 기능을 위해 특정 구조적 특징이 필수적인 근골격계 조직에서 매우 중요하다. 근골격계 조직은 특정 기계적, 생화학적 및 계층적 조직으로 구성된 복잡한 구조를 가지고 있다. 이전의 여러 연구에서 생체 활성 및 기계적 자극으로 향상된 기계적 특성을 보고했지만, 자가 조립 기술만으로 근골격계 조직의 복잡한 구조 및 기능을 달성하는 것은 어려울 수 있다. 따라서 본 논문의 주요 목적은 (1) 자가 조립된 중간엽 줄기세포 (MSC) 응집체를 개발하고, (2) 탈세포화 생체재료를 추가하여 MSC 응집체의 제형을 수정하고, (3) 다양한 근골격계 적응증을 가진 동물 모델에 적용하여 조직 재생 가능성을 평가하는 것이다. I 장에서는 생체 모방 결합 이식편의 사용이 외부 스캐폴드 없이 이식편의 치유를 촉진할 것이라고 가정했다. 결합조직 성장인자 (CTGF) 와 전환성장인자 (TGF-β) 의 적용은 스캐폴드가 없는 구조에서 섬유연골의 발달로 이어졌다. 힘줄 표면에 콜라게나제를 적용하면 힘줄 이식편과 세포의 통합이 개선되었다. 섬유연골로 분화된 구조체와 힘줄의 콜라게나제 처리의 조합은 뼈-인대 사이조직 치유와 관련하여 자연 힘줄에서 볼 수 있는 것과 유사한 치유 결과를 가져왔다. 또한, 시험관 내 및 생체 내 실험 모두에서 이 접근법이 현재의 표준적인 힘줄 재생 방법과 비교할 때 향상된 생체역학적 강도를 입증한다는 것을 보여주었다. 전반적으로, 스캐폴드 없이 제작된 섬유연골 구조체의 이식과 힘줄 콜라게나제 처리의 조합은 현재의 힘줄 및 인대 복원을 향상시키기 위한 유망한 생체 모방 접근법을 제시한다. II 장에서는 구역별로 탈세포화된 연골판 세포외 매트릭스 (DMECM) 와 활막유래 줄기세포(SMSC)를 사용하여 자가조립 공법으로 제작된 반월판 미세조직이 부분적으로 연골판이 절제된 돼지의 연골판 치유를 촉진할 수 있는지 조사했다. 자가조립 기술은 가교제의 추가 없이 구성 요소가 균일하게 분산되는 것을 특징으로 하는 탄력적인 조직 구조체를 제작하게 했다. 또한 자가조립은 연골판에서 파생된 다양한 생체 재료를 추가하는 것과 유사하게 조직 성숙을 촉진했다. 구체적으로 내부 반월판 유래 생체재료를 첨가하면 연골과 유사한 구조체, 외부 반월상 연골 유래 생체 재료를 추가하면 인대와 같은 특성을 나타내는 구조체가 형성되었다. 우리는 추가적인 성장 촉진제를 처리하지 않고도 이를 수행할 수 있었다. 그 후, 부분 반월판 절제술 모델에서 의도적으로 생성된 반월판 병변을 채우는 데 미세 조직을 활용했다. 조직학적 분석 결과에서 반월판 미세조직을 이식한 그룹에서는 반월상연골의 내측 및 외측 고유 조직과 유사한 조직 복원이 이루어졌다. 반월판 미세조직을 이식한 군은 고유 조직 대비 약 70~80% 정도의 간접 및 직접 생체역학적 수치를 나타내는 것으로 확인되었다. III 장에서는 3D 바이오 프린팅을 위한 바이오잉크로서의 연골탈세포화 생체재료 유도 자가 응집체인 DSA의 타당성과 DSA 바이오잉크를 사용하여 제작된 구조체의 연골 치유 가능성을 조사했다. 생물학적 특성 분석 결과, 연골과 관련된 유전자 및 단백질 수준이 세포 자가 응집체 (SA) 및 단순 세포-연골탈세포화 생체재료 혼합 물질 (DMC) 그룹에 비해 DSA 그룹에서 크게 증가한 것으로 나타났다. 주로 살아있는 세포로 구성된 DSA 바이오잉크는 세포 생존력의 현저한 감소 없이도 기존 바이오잉크에 필적하는 안정적인 인쇄능을 보여주었다. 돼지의 무릎 관절 내 Trochlea에 DSA 바이오잉크를 사용하여 프린팅 된 구조체를 이식한 그룹의 조직학적 결과는 결함 그룹에 비해 높은 수준의 글리코사미노글리칸 (GAG) 및 II형 콜라겐 침착으로 연골 유사 조직의 형성을 보여주었다. 프린팅된 구조체를 이식한 그룹의 기계적 평가 결과 또한 결함 그룹에 비해 현저하게 높은 압축 특성을 보였다. 전체적으로, 이 연구는 3D 바이오프린팅을 위한 DSA 바이오 잉크의 성공적인 개발을 강조하며 이를 활용해 프린팅된 구조체를 이식한 돼지의 조직학 및 생체역학 결과가 결함 그룹에 비해 향상됨을 보여주며 DSA 바이오잉크의 연골 재생 가능성을 보여준다. 결론적으로, 본 연구는 섬유연골 분화를 유도하는 두 가지 성장인자를 이용하여 세포시트를 제작하고 이를 활용하여 뼈-인대 사이의 생체조직을 모방하였다. 또한, 활막유래 줄기세포와 구역별 탈세포화 반월판 생체재료를 자가조립하여 반월판 미세조직을 제작하고 이의 치료 효능을 부분 반월판 절제술 모델에서 검증하였다. 최종적으로 성장인자 및 가교제가 없는 조건에서 전성숙된 연골 자가조립체를 바이오잉크로 개발하고 이의 연골 결손 치유 가능성을 확인하였다. 본 연구 결과들을 기반으로 하여 자가조립 구조체의 간단한 적용, 가교제와 성장인자를 제외한 제작 과정 및 환자 맞춤형 인공 조직의 제작을 통해 임상적 적용 가능성이 향상될 것으로 기대된다.|Regenerative medicine and tissue engineering both aim to restore or substitute the function of biological tissues by way of fabricating tissue and organ constructs in vitro. Self-assembly technologies offer advantages such as biomimicry, scalability, and adaptability for multiple cell groups, harnessing the innate capability of cells to organize into functional tissues. This technology holds promise for producing structures that closely resemble native tissues with regard to its composition and functionality. The enhanced biomimicry is crucial for development of optimally engineered tissues, especially in musculoskeletal tissues, where specific structural features are essential for proper function. Musculoskeletal tissues have complex structures with specific mechanical, biochemical, and hierarchical organizations. Although several previous studies reported enhanced mechanical properties with bioactive and mechanical stimuli, achieving the intricate architecture and functionality of musculoskeletal tissues through self-assembly alone can be challenging. Therefore, the primary aim of this dissertation is to: (1) develop the self-assembled MSC aggregates; (2) modify the formulation of MSC aggregates by adding dECM; and (3) evaluate its potential for tissue regeneration by applying it to animal models with various musculoskeletal indications. In chapter I, we hypothesized that the use of a biomimetic enthesis graft would promote graft healing without an external scaffold. The application of both CTGF and TGF-β led to the development of fibrocartilage in the cell-based microtissues. The application of collagenase to the surface of the tendon led to an enhancement in the integration of cells with the tendon implant. The combination of fibrocartilage microtissues and collagenase employment of tendons yielded comparable healing outcomes to those seen in natural tendons with regards to BTI (bone-tendon interface) healing. Additionally, in vivo as well as in vitro experiments showed the approach demonstrated enhanced mechanical robustness when in comparison with existing standard tendon repair method. Overall, the combination of fabrication of cell-based fibrocartilage microtissues without scaffold with tendon collagenase employment presents a promising biomimetic approach for enhancing current tendon and ligament restorations. In chapter II, we investigated whether self-assembled meniscal microtissues fabricated by using acellular meniscal extracellular matrix (DMECM) and synovial membrane-derived stromal cells (SMSCs) could promote the healing of the meniscus of partially meniscectomized porcines. The self- assembly techniques resulted in the development of a resilient tissue microtissues characterized by the uniform dispersion of constituents with no addition of a crosslinker. The self-assembly also facilitated tissue maturation, resembling the addition of a variety of biomaterials derived from the meniscus. Specifically, the addition of interior meniscus-derived biomaterial resulted in the formation of microtissues resembling cartilage. On the other hand, the addition of exterior meniscus-derived biomaterials resulted in the formation of microtissues displaying ligament-like properties. We were able to do this in the absence of employment with any additional growth agents. Subsequently, the microtissues were utilized for filling lesions at the meniscus that were intentionally produced in a partial meniscectomy minipig model. As a result, the group with implanted meniscal microtissues resulted in tissue restoration that is similar to that corresponding to the respective meniscus zones observed in microscopical examination with histology. The group implanted with meniscal microtissues exhibited values of about 7–80% of the indirect and direct biomechanical experimental scores compared to native tissue. Therefore, we anticipate that the clinical applicability of self-assembled microtissues will be enhanced by (1) the simple application, (2) personalized properties, and (3) the fabrication process, except for crosslinkers and chemical cues. In chapter III, we investigated (1) the feasibility of DCECM-guided self-assembled microtissue (DSA) composites as bioink for 3D bioprinting and (2) the cartilage healing potential of printed constructs using DSA bioink. Analysis of biological properties demonstrated that gene and protein levels related to cartilage increased significantly in the DSA group relative to the SA and DMC groups. DSA bioink, which consisted predominantly of living cells, demonstrated stable printing capabilities comparable to conventional bioink without showing significant decreases in cell viability. Histological results of the group with the implantation of a printed construct using DSA bioink into the porcine trochlea groove of the knee joint demonstrated the development of tissue resembling cartilage with elevated levels of GAGs and type II collagen accumulation against the defect group. Mechanical evaluation of the group with the implantation of the printed construct also exhibited significantly elevated compressive properties compared to the defect group. In all, the study highlights the successful development of DSA bioink for 3D bioprinting, demonstrating its potential for cartilage regeneration with enhanced structural and functional outcomes.
학위논문(박사)--의생명과학과,2024. 2
Keywords: Bone-to-tendon interface; Cartilage; Decellularized extracellualr matrix; Fibrocartilage; Mesenchymal stem cells; Self-assembly